Live biotherapeutic products: a capstone for prevention of recurrent Clostridiodes difficile infection - Sehgal, Kanika; Feuerstadt, Paul (Frontiers in Microbiomes, 2024)
Clostridiodes difficile infection (CDI) continues to be one of the leading causes of healthcare-acquired diarrhea and infections, and recurrence is the biggest challenge in its management. As technology and research have led to a better understanding of the pathophysiology of C. difficile, we have come to appreciate the role that the gastrointestinal microbiota plays in infection onset and the prevention of recurrence. The gut microbiota is disrupted in those with CDI, which allows further propagation of the infection leading to recurrence, if the microbiota deficiency is unable to regrow itself. While antimicrobial therapy is necessary for treatment of any CDI, these therapeutics do not address the underlying disturbance of microbiota. Microbial remodulation therapies have been developed supplementing the microbiota deficiency that exists after the standard of care antimicrobial resulting in a reduction of recurrence. Fecal microbiota transplantation (FMT) was the initial attempt for this type of therapeutic and proved to be safe and effective, however never achieved FDA approval. In light of this, live biotherapeutic products (LBPs) were developed by pharmaceutical companies through a more standardized and regulated process. These products are safe and efficacious in reducing CDI recurrence when given after a standard of care antimicrobial, eventually leading to FDA approval of two products that can now be used widely in clinical practice.